Bandgap alignment of α-CsPbI3 perovskites with synergistically enhanced stability and optical performance via B-site minor doping. (July 2019) - Fang, Zhi; Shang, Minghui; Hou, Xinmei; Zheng, Yapeng; Du, Zhentao; Yang, Zuobao; Chou, Kuo-Chih; Yang, Weiyou; Wang, Zhong Lin; Yang, Ya
Abstract: A relatively wide bandgap and intrinsically phase instability of α-CsPbI3 perovskites (PVSKs) greatly hinder their potential applications in solar cells. One of the popular solutions is based on high-concentration doping, which however encounters big difficulty in the balance between phase stability and optical performance. Here, we report the advance on bandgap alignment of CsPbI3 through B-site (Pb 2+ cation) minor doping engineering employing density functional theory (DFT). It is discovered that the bandgaps could be finely aligned by minor doping of Si 2+, Sn 2+ and Ge 2+, which is caused by the downshift of conduction band minimum contributed by B- p orbital level within CsPb1- x B x I3 PVSKs, and thus offer shrunken gaps and enlarged imaginary part of dielectric function for enhanced photo absorption. Furthermore, the minor doping of Sn 2+ could not only bring a suitable tolerance factor for CsPbI3 with a slighter lattice distortion, but also increase the charge density of Pb 2+ to enhance the interaction between Pb 2+ and I −, which consequently improve their structure stability. Graphical abstract: We reported the advance on bandgap alignment of α-CsPbI3 perovskites (PVSKs) through B-site minor doping engineering with synergistically enhanced stability and optical property, which was predicted by density functional theory calculation. The present work establishes the rule that the bandgaps of α-CsPbI3 PVSKs decrease with the sequential change of dopants from Ge, to Sn and then to Si at a fixed doping level, and reduce with the raise of doping concentrations for a given dopant, suggesting the bandgap engineering of PVSKs via B-site minor doping strategy. Furthermore, it is discovered that minor doping of Sn 2+ with an optimal concentration 2.8 at. % could not only bring a suitable tolerance factor for CsPbI3 PVSKs with a slighter lattice distortion, but also increase the charge density of Pb 2+ to enhance the interaction between Pb 2+ and I −, which consequently improve their global stability. Current work might direct and advance the exploration of novel PVSKs with totally improved performance, which could inspire their future applications in efficient solar cell. Image 1 Highlights: We reported, for the first time, B-site minor doping engineering of CsPbI3 perovskites. The perovskite bandgaps have been finely aligned by B-site minor doping of Sn 2+, Ge 2+ and Si 2+ . Minor doping of 2.8 at. % Sn 2+ could enhance the stability and optical performance synergistically. The deeply physics of B-site minor doping engineering of perovskites has been proposed.